EFFECT OF SALINITY ON SPECIFIC GROWTH RATE AND CANNIBALISM OF TAMBAQUI (Colossoma macropomum) JUVENILES IN A CONTROLLED ENVIRONMENT - Ramadhani, Gilbran Muhammad; Pratiwy, Fittrie Meyllianawaty; Iskandar, ,; Herawati, Titin (Jurusan Perikanan dan Kelautan, 2025)
The objective of this study was to analyze the effect of salinity on the reduction of cannibalism in tambaqui juveniles and their specific growth rate. The study lasted for 35 days. The research method used was a completely randomized design (CRD) experiment with two treatments and six replications. The treatments were (A) no salinity and (B) salinity at 5 ppt. The parameters observed in this study were specific growth rate, survival rate, cannibalism, and water quality. The results showed that using 5 ppt salinity (B) reduced cannibalism in tambaqui juveniles, while specific growth rate and survival rate did not differ significantly between treatments. Keywords: Tambaqui, cannibalism, salinity, survival rate.